Anatomical assessment by cone beam computed tomography with the use of lateral cephalograms to analyse the vertical bone height of the anterior palate for orthodontic mini‐implants. (15th July 2020) - Möhlhenrich, Stephan Christian; Kniha, Kristian; Peters, Florian; Chhatwani, Sachin; Prescher, Andreas; Hölzle, Frank; Modabber, Ali; Danesh, Golamreza
Abstract: Objective: Lateral cephalograms (LC) should be usable to evaluate the vertical bone height of the anterior maxilla for planning the placement of orthodontic mini‐implants (OMI). The purpose of this study is to determine the usability of LC for examining the real vertical dimension of the anterior palate. Setting and Sample Population: Lateral cephalograms and corresponding cone beam computed tomography (CBCT) scans were employed for examining 30 fresh cadaver heads. Materials & Methods: The minimum (distance A) and maximum (distance B) vertical palatal bone heights on LCs at the level of first premolars were measured, whereas the corresponding measurements were taken via CBCTs on the median, and 2‐, 4‐ and 6‐mm paramedian planes. Additionally, the overall minimum vertical palatal height on CBCT was recorded. Results: Distance A and B on LC were about 8.3 ± 2.5 mm and 9.9 ± 2.5 mm, respectively. The median palatal height on CBCT was significantly higher than both measurements on LC ( P  < .01). Furthermore, the bone supply on the paramedian planes was similar or higher on CBCT compared to Distance A and similar or less compared to Distance B. The strongest correlation at the level of the premolars was found in the comparison of the maximum vertical palatal height via LC with the vertical palatal height on the median plane via CBCT ( r  = .84, 95% CI: 0.69‐0.92, P  < .001). Conclusions: In order to make the best possible use of the vertical bone supply of the anterior palate and to avoid injuries to the nasal floor, Distance A should be taken into account for planning paramedian OMI placements and distance B for median OMI insertion.